The narcissistic personalities of mothers as perceived by their daughters and its relationship to emotional balance among female students at King Faisal University - Entesar Alnashmi; Hanem M. Alboray (Frontiers in Psychology, 2025)
IntroductionThis study explores how female university students perceive their mothers’ narcissistic traits and investigates the relationship between these perceptions and the students’ emotional balance.MethodsA descriptive correlational design was used. The sample included 416 female students aged 18 -24 from King Faisal University. Two tools were utilized: the Narcissistic Mother Scale and the Emotional Balance Scale developed by the researcher.ResultsOverall, students perceived their mothers’ narcissism as low, except for the “excitability” dimension, which scored moderate. Emotional balance levels among students were also moderate. A significant negative correlation was found between perceived maternal narcissism and emotional balance. “Intolerance” was the strongest predictor of emotional imbalance, followed by “exploitative Ness.”DiscussionThese findings suggest that higher levels of perceived maternal narcissism may negatively influence daughters’ emotional balance, highlighting the potential impact of maternal personality traits on young women’s emotional development.